Implementation of the Electronic Information and Transactions Law in Encouraging Responsible and Intelligent Use of Social Media Among Senior High School Students in Palangka Raya - Tabang, Valentino; Firman, Firman; Tampubulon, Benget (Jurnal Lingua Idea, 2025)
This study aims to analyse the level of awareness and application of the Electronic Information and Transactions Law (commonly referred to as the ITE Law) and digital ethics among senior high school students. Employing a qualitative approach with a descriptive research design, the study seeks to gain a comprehensive understanding of how the ITE Law is implemented and how ethical awareness is fostered in students’ use of social media. This methodological approach was selected to obtain a holistic and in-depth portrayal of students’ attitudes, comprehension, and behaviours concerning social media regulations and digital conduct. The research subjects consist of students and teachers from a senior high school in Palangka Raya, while the object of the study is the application of the ITE Law within the context of cultivating responsible digital behaviour in the school environment. Data collection techniques included in-depth interviews with selected teachers and students, observations of student activities both inside and outside the classroom, and document analysis of relevant materials such as school regulations and socialisation resources related to the ITE Law, particularly those used during school orientation programmes (Introduction to School Environment Program) and guidance counselling sessions. The research instruments comprised interview protocols, observation sheets, and documentation checklists. The data were analysed qualitatively using the interactive model proposed by Miles and Huberman, which encompasses three key stages: data reduction, data display, and conclusion drawing and verification. Through this analytical process, the researcher sought to identify patterns, themes, and meanings within the collected data, which were subsequently presented in the form of descriptive narratives. This approach enabled an exploration of the complex and context-specific social realities surrounding students’ legal awareness and ethical considerations in the use of social media.